Eco-friendly modification of earthen construction with carrageenan: Water durability and mechanical assessment - Nakamatsu, J (2017)
This research was carried out by the Research Group of Materials Modification at PUCP. The authors would like to acknowledge the Pontificia Universidad Católica del Perú PUCP and its funding office DGI-PUCP (project 2013-0061) for providing funds to the project within which this work was developed. The forth author would also like to thank the fellowship funding for postgraduate studies by CONCYTEC, PERU (Contract N° 012-2013-FONDECYT). Finally, the authors thank the Soils Laboratory of the Civil Engineering Department at PUCP for the availability of their installations and equipment, and Manuel Otero, for providing the carrageenan extract for this study.